Predictors for Deformity Progression in a Spinal Muscular Atrophy Cohort After Scoliosis Correction Surgery. Issue 8 (October 2020) - Shen, Po-Chih; Lu, Cheng-Chang; Liang, Wen-Chen; Tien, Yin-Chun; Jong, Yuh-Jyh; Lu, Yen-Mou; Liu, Zi-Miao; Shih, Chia-Lung; Chou, Shih-Hsiang
Abstract : Study Design: This was a single-center, retrospective study. Objective: The objective of this study was to assess the risk factors for deformity progression after scoliosis correction surgery in spinal muscular atrophy (SMA) patients. Summary of Background Data: Moderate residual postoperative scoliosis curve is common in SMA populations; however, the acceptable postoperative scoliosis curve for preventing deformity progression remains uncertain. Materials and Methods: Twenty-nine SMA patients undergoing scoliosis correction surgery were included. Scoliosis progression was defined as an increase of 10 degrees in the major curve of Cobb angle (MCCA); pelvic obliquity (PO) or concave-side hip progression was arbitrarily defined as an increase of ≥1 grade after surgery. Risk factors for deformity progression were examined using Cox proportional hazard models. The cumulative incidence rate of deformity progression was performed by the Kaplan-Meier survival analysis Results: The mean age at surgery was 13.3 years (range: 8–25 y) and the mean follow-up time was 7 years (range: 2–22.9 y). The mean MCCA was corrected from 69 to 34.6 degrees at initial follow-up and 42.2 degrees at the final follow-up. Postoperative MCCA ( P =0.002) and PO ( P =0.004) at initial follow-up were the risk factors for scoliosis progression. Postoperative MCCA at initial follow-up ( P =0.007) and age at the time of surgery ( P =0.017) were the risk factors for PO progression. Different cutoff points of postoperative MCCA at initial follow-up were compared for predicting deformity progression. We found the patient with postoperative MCCA of <30 degrees at initial follow-up had a significantly less cumulative incidence rate of progression than their counterparts for scoliosis ( P =0.005), PO ( P =0.023), and concave-side hip progressions ( P =0.008). Conclusions: We recommended that MCCA should be corrected to <30 degrees to prevent postoperative scoliosis, PO, and concave-side femoral head coverage percentage progressions. Patients receiving surgery earlier had less postoperative MCCA at initial follow-up but with no increase in the risk of postoperative scoliosis progression.